Tipologi Permukiman Kawasan Karst Desa Beketel Kecamatan Kayen Kabupaten Pati - Anatasari, Ayu Tri; Pradoto, Wisnu (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2016)
Karst region village Beketel show growth and development of the settlements, it is marked by the increasing number of houses that are in the area. The increase in population resulted in more and more people are using the karst region Beketel village to settle and reside. socio-economic constraints of low income earners, as well as heredity and family that causes them choose to stay at home is simple with limited infrastructure is not adequate influenced by the physical condition of karst region. In looking at the settlement typology of karst areas Beketel Village methodology of the research is to Diskriptif Qualitative methods. To know the typology of the village settlements in the karst region Beketel, can be identified through a settlement typology approach by looking at the elements of the settlement, the settlement eksisiting conditions, condition of facilities working paper, the tendency of society in the living, as well as settlement patterns are formed. The final results obtained from studies typology settlement karst region village beketel districts Kayen district starch is a settlement patterns closer to the sources of clean water are affected by the condition of the availability of clean water sources, settlement patterns spread is influenced by the physical condition of nature that makes people choose to stay in the valley between karst hills, as well as settlement patterns formed extends all the way because of the orientation of building a house facing to the road as well as their kinship that makes people build houses adjacent to relatives who still has a relationship kinship.